Educational level and first-time PSA testing in general practice. (3rd September 2019) - Lerhmann-Lerche, Caroline Sophie; Larsen, Signe Benzon; Andersen, Ingelise; Thygesen, Lau Caspar; Kaae Andersen, Klaus; Duun-Henriksen, Anne Katrine; Johansen, Christoffer; Røder, Martin Andreas; Brasso, Klaus; Dalton, Susanne Oksbjerg
Abstract: Introduction: Different patterns in the use of prostate-specific antigen (PSA) testing might explain socioeconomic differences in prostate cancer incidence and mortality. We examined the association between socioeconomic position, measured as education and first-time PSA testing in general practice. Material and Methods: A population-based cohort study of men aged 45–79 years without prior prostate cancer diagnosis living in the Capital Region of Denmark between 2000 and 2014. Information on socioeconomic indicators (education, income, cohabitation status and work market affiliation), prostate cancer diagnoses, and vital status were obtained from national registries. Date of first PSA test was obtained from the Copenhagen Primary Care Laboratory database. Temporal trends of PSA testing were calculated as annual age-standardised incidence rates and the association was examined by a multivariable Cox proportional hazards model. Results: The cohort consists of 431, 997 men of which 105, 476 (24%) had a first-time PSA test in the study period. Men with longer education, higher income, living with a partner, and employed had higher rates of PSA testing. For men with short education, the rate of PSA test was 28.3 tests per 1000 person-years compared to 31.2 tests among men with long education. The fully adjusted hazard ratio for a first PSA test among men with short education was 0.87 (95% CI, 0.85–0.89) compared to men with long education. Conclusion: The association between education and first-time PSA testing indicates socioeconomic disparities in health care utilisation, which could explain part of the observed socioeconomic difference in prostate cancer incidence and mortality.